Konsep Pajak Dalam Kitab Al-Kharaj Abu Yusuf : Relevansi dengan Sistem Perpajakan di Era Globalisasi - Fiqha Aulia Achsam; Hasmira Rahmadani; Riska Salim (Jurnal Ekonomi dan Bisnis Digital, 2024)
As a widely known figure, Abu Yusuf has written a phenomenal work in the study of taxation, namely the book al-Kharaj. This book, written at the request of Caliph Harun ar-Rasyid, is used as a guide in tax management efforts. As one of the crucial sectors of state revenue, taxes should not deceive the public from their percentages. This article aims to determine the context of the book al-Kharaj and its contents. Therefore, this study attempts to reveal Abu Yusuf's thoughts and background which are traced through his attitudes, writings and responses to a case that occurred at that time. Apart from that, this article also aims to understand the tax concept initiated by Abu Yusuf and its practice in current economic conditions. This study found that Abu Yusuf's thinking about taxes is a concept that is still used today. This concept is applied in determining the percentage of tax revenue by the state. The al-Kharaj concept is also used in the land and building tax (PBB) sector and customs revenues.